Skrining dan Edukasi Anemia Pada Remaja Putri di Sekolah Menengah Pertama Muhammadiyah 1 Gamping - Yanita Trisetiyaningsih; Hutasoit , Masta; Yati, Dwi; Supadmi, Fransisca Romana Sri (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Anemia is a condition in which the level of hemoglobin in the blood is less than normal. Adolescent girls are a group that is prone to anemia due to several factors including malnutrition, menstruation, socioeconomic status and adolescent knowledge. Providing education is one way to increase adolescent knowledge related to anemia in adolescents. This service activity will be carried out at SMP Muh. 1 Lime. This activity begins with the preparation stage, coordinates and prepares facilities and infrastructure, the implementation stage begins with the pretest and the provision of education using animated videos, as well as posttest. The final stage is reporting activities and follow-up plans. This activity is a follow-up to research that has been carried out in 2021 with the title